"Assistive Devices" Learning Object - Osvaldo Rodriguez; Jorge Ruiz; Francois Phancao (Association of American Medical Colleges, 2007)
Abstract This resource is an interactive multimedia tutorial on the basic characteristics, rationale, indications, and contraindications of the use of assistive devices for ambulation. The learning activity was primarily developed as a self-learning tool. It can be used to reinforce knowledge or skills if used in conjunction with preceptor-assisted activities (i.e., lectures, workshops), or as a refresher for learners in the clinical environment immediately before performing this assessment in the home. The tutorial takes approximately 20 minutes to complete and requires an internet browser with Flash Player 6 or later.